Insights for the development of specific kinase inhibitors by targeted structural genomics. - Fedorov, O; Sundström, M; Marsden, B; Knapp, S (2007)
Many protein kinases are validated intervention points for drug development, however active site similarities often lead to a lack of selectivity and unwanted side effects in the clinic. To address this issue, it is desirable to increase the number of high resolution crystal structures and complexes with non-adenosine ligands available for the rational design of more selective inhibitors. Recent progress in protein crystallography and biotechnology has enabled structural genomics projects to target challenging proteins successfully, including protein kinases. As we discuss here, this effort has resulted in a considerable increase in the number of available high resolution structures and inhibitor complexes and has identified novel structural motifs that are available for drug development.